Instagram Application and Its Role in Creating Purchasing Decision Determinants - saragih, megasari gusandra; Astuti, Desi; Ichsan, Ichsan; Vydia, Vensy; Santoso, Aprih (Universitas Dharma Wacana, 2023)
Presently, the rapid advancement of technology is ongoing, and digital platforms have become an omnipresent resource for professionals in business, forming an integral part of a holistic marketing strategy. Social media is now used to introduce a product or service from a company, organization, or government. Along with the development of technology and information, nowadays many online shops have sprung up in various groups, from teenagers to adults. One of local company that uses Instagram social media to spread information about their company's products is Erigo. This study aims to analyze and examine the factors influencing of brand image, information quality and celebrity endorser on purchasing decisions of Erigo Brand product in Instagram. The study utilized quantitative methods along with regression analysis techniques for its research methodology.. The sampling method used purposive sampling and the number of samples used in this study amounted to 80 respondents source was distribution online questionnaires via WhatsApp to customers who had purchased Erigo brand products through Instagram. The data were analyzed with SPSS’ 26 and was carried out by several tests such as test : validity, realibility, classic assumption, linear regression analysis and coefficient of determination. The results that the brand image, information quality and celebrity endorser have a significant and positive effect partially or simultaneously on purchasing decisions of Erigo brand product. Meanwhile, brand trust can provide the most dominant influence on purchasing decisions of Erigo brand products.